Oral care and the use of bone-targeted agents in patients with metastatic cancers: A practical guide for dental surgeons and oncologists - Kuchuk, Iryna (J Bone Oncol, 2013)
BACKGROUND: Bone-targeted agents such as bisphosphonates and the RANKL antibody have revolutionised the care of patients with bone metastases. There has, however been increasing concern about the oral health of these patients and in particular osteonecrosis of the jaw (ONJ), especially with the increasing use of these agents at higher potencies for greater periods of time. METHODS: A review of the published data in PubMed and meeting abstracts was performed to examine incidence, risk factors, pathogenesis, clinical course and management of osteonecrosis of the jaw with focus on cancer patients treated with bone-targeted agents (BTA) for bone metastases. This manuscript takes the most frequent and pertinent questions raised by oncologists, dentists and oral and maxillofacial surgeons and tries to give a pragmatic overview of the literature. RESULTS: The incidence of ONJ varies depending on types of bone-targeted agents, duration of treatment and additional risk factors. The causes and pathogenesis of ONJ is not fully elucidated, however bone-targeted therapy induced impaired bone remodelling, microtrauma secondary to jaw activity, and oral bacterial infection seem to be important factors. Since the treatment options for ONJ are limited and not well established, preventive strategies have to be included in patients management. CONCLUSIONS: Many unanswered questions remain about the optimal oral care of patients receiving bone-targeted agents. Prospective data collection will remedy this and help to provide practical guidelines for the management and treatment of those patients that require dental intervention.